Development and evaluation of a distance education in general surgery in Zamboanga City Medical Center - Joson, Reynaldo O.
Distance education (DE) is a trend in education in general and it is starting to become a trend in medicine. Telemedicine is very popular. At present, however, DE is used mainly in continuing postgraduate medical education. There are only a few reports on the use of DE in undergraduate medical education and specialist training. In the Philippines, there is no report on the use of DE in the training of general surgeons.Zamboanga City Medical Center's (ZCMC) Department of Surgery had no structured training program in 1991. It lacked residential trainors with only one PBS diplomate in Zamboanga City and in the entire Western Mindanao region. In 1991, the ZCMC administrators felt the need to upgrade its general surgery training program with the help of Manila faculty.An action research was done to solve the problem of ZCMC's Department of Surgery using the following five steps, namely: diagnosis, analysis, feedback, action, and evaluation. The action made use of distance education as a strategy to bring about the needed change.The general objective was to develop and evaluate a distance education in general surgery in ZCMC.The specific objectives were:1. To initiate and develop a distance education in general surgery in ZCMC.2. To evaluate the distance education in general surgery in terms of context, input, process, and product.3. To determine whether a distance eduation in general surgery can upgrade a training program in a Philippine regional hospital lacking in residential trainors.The distance education in general surgery was in response to the need of ZCMC to upgrade its general surgery training program with the help of Manila faculty.Using the distance education mode, the Manila faculty, usually two at a time, initially went to ZCMC every three months. Later, they went every month for a total period of four years, staying for about 2 days each time, to conduct and monitor the training program. During the intervals, the Manila faculty provided printed materials for self-directed study under the guidance of a local supervisor. Ten audioteleconferences were held on the last year of the program.The 4-year course started with 13 trainees and ended with nine graduates, four practicing in Zamboanga City and five in the neighboring cities and provinces in Western Mindanao. Conclusions: 1.The distance education in general surgery had upgraded the general surgery training program of ZCMC.Bases: Presence of a written structured curriculum having satisfactory context, input, and process evaluation.2. The distance education in general surgery had produced competent surgeons who in turn had rendered better patient services.Bases: Evaluation given by key hospital people.3. The distance education in general surgery had facilitated the PCS accreditation of the ZCMC's Department of Surgery training program.Bases: The program of the ZCMC's Department of Surgery that was accredited by the PCS in 1996 was an aftermath of the distance education from 1991 to 1995.4. The distance education in general surgery had solved the problem and need of ZCMC's Deparment of Surgery.Bases: Upgraded ZCMC general surgery training program with competent surgeons, better patient services, and accredited by the PCS, the expressed needs of ZCMC administrators.5. The distance education can upgrade a training program in a government regional hospital lacking in residential trainors.Bases: Upgraded ZCMC general surgery training program effected by a curriculum that followed the concept and process of a distance education.Conclusions: 1.The distance education in general surgery had upgraded the general surgery training program of ZCMC.